(untitled) (CAHIERS MAGELLANES-NS, 2024)
The new Internet setting and frequent technical upgrades have caused libraries to rearrange and become accustomed to these innovations for a more efficient system and service performance. It is critical to escalate the use of library materials and services, which can be accomplished with the help of good marketing tactics. Marketing has become an increasingly important tool for promoting libraries and their services to users in today's rapidly evolving digital environment. The library must market itself to be proactive and meet the needs of its users. The purpose of this paper focus on the views of librarians about the marketing of library resources and services and to review its role in the usage of libraries. It also discusses what modern library services are, and how to promote and advertise those using digital technologies, including some of the most useful digital tools. Librarians should view the digital era as an opportunity rather than a threat for marketing their products and services. The present research is a survey method in which a questionnaire used as a tool for data collection and a Likert scale is used for interpreting the collected data. “Marketing of library resources and services is a major area which needs to be focused upon and if implemented accurately, it will surely motivate the patrons to walk towards the libraries”, is one of the major findings on this research.